Komunikasi Interpersonal Jarak Jauh : Dampak Smartphone dalam menjaga Hubungan Baik Orang tua dengan Anak - Dwi Israfi Parangin angin; Azhar, Anang Anas (eScience Humanity Journal, 2024)
This research aims to determine the impact of smartphones in maintaining parent-child relationships through long-distance interpersonal communication for students of the Communication Science Study Program, North Sumatra State Islamic University. This research uses a qualitative approach. For data collection, the author used direct interviews, indirect interviews via WhatsApp social media and literature studies. The results of this research include; 1) Long distance interpersonal communication between parents and children via smartphone; (a) monitor the progress of children's studies; (b) health condition; (c) monitoring children's relationships with friends; (d) maintaining openness between children and their parents; (e) monitor financial conditions. 2) Intensity of media use 3) Media and its features 4) Impact of smartphones in maintaining good relationships between parents and children in long distance conditions: 1.1 Positive impact; a) Increasing close relationships b) Ease of access to information; c) Openness and trust 1.2 Negative impacts; a) as if there is no news, the child forgets to tell the parents; b) network or signal interference from both parties; c) miscommunication or misunderstanding in conveying the message; d) applications that must be updated. This research suggests a balanced approach to smartphone use is essential for parents and children to remain emotionally connected and maintain a healthy relationship. Keywords: Interpersonal communication; Long distance; Impact of Smartphones; Connection; Parents with children